PENGAMBILAN KEPUTUSAN WISATAWAN DIMENSI BUDAYA UNCERTAINTY AVOIDANCE - Mahardika, I Made Ngurah Oka (Guna Sewaka, 2023)
The purpose of this article is to analyze the decision-making process of tourists when visiting culturally-based tourism objects. The approach chosen is to use a literature review. When choosing a destination, tourists are strongly influenced by Hofstede's cultural aspects. Cultural dimensions consist of power distance, individualism, masculinity, uncertainty avoidance, and long-term orientation. To avoid uncertainty, tourists tend to choose cultural destinations where they feel safe, comfortable and risk-free. Moreover, the motivations of tourists to decide to visit a tourist destination are strongly influenced by push and pull factors.